Delayed Convulsions and Brief Contralateral Hemiparesis After Retrobulbar Block. Issue 3 (1st May 2006) - Pragt, Elien; van Zundert, André A.J.; Kumar, Chandra M.
Abstract : Objective: This case report describes convulsions and hemiparesis after retrobulbar injection with good outcome in a patient undergoing outpatient cryocoagulation of his right eye. Case Report: We report a young man in which localized convulsions of the ipsilateral face occurred 9 minutes after retrobulbar injection followed shortly by convulsions of the contralateral arm and leg. After the convulsions, the patient experienced left-sided hemiparesis resolving approximately 1 hour after the injection. There was no hemodynamic instability during this period. It was difficult to determine the exact cause of convulsions and hemiparesis. Conclusions: We believe these complications occurred because of unintentional injection of local anesthetic agent into the subarachnoid space without affecting the brainstem. Possible mechanisms of spread of local anesthetic agent into the central nervous system after retrobulbar block are discussed.